2019
DOI: 10.1088/1612-202x/ab4806
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Pseudomonas aeruginosa bacterial biofilms using new polycationic photosensitizers

Abstract: The treatment of infected, long-term, non-healing, complicated wounds of the skin and mucosa, trophic ulcers, pressure sores and ulcers of diabetic feet represents a serious problem, especially in the case of resistant and multi-resistant pathogens. Antibacterial photodynamic therapy can be a promising method of local infected foci treatment of such diseases.This work is devoted to the study of the possibility of photodynamic inactivation (PDI) of Pseudomonas aeruginosa bacteria in the form of biofilms with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Many PDA problems require the PS excitation in thin (≤ 5 mm) layers of sensitized aqueous compositions. Such problems include photodynamic inactivation of pathogens -viruses or bacteria, on various surfaces [8,9], in vitro screening studies of PS properties [10,11]. For small layer thicknesses and low (less than 10 μM) PS concentrations used for such a PDA, a significant part of the light in the spectral range of the PS absorption band can pass through the layer without participating in the PDA process.…”
Section: Introductionmentioning
confidence: 99%
“…Many PDA problems require the PS excitation in thin (≤ 5 mm) layers of sensitized aqueous compositions. Such problems include photodynamic inactivation of pathogens -viruses or bacteria, on various surfaces [8,9], in vitro screening studies of PS properties [10,11]. For small layer thicknesses and low (less than 10 μM) PS concentrations used for such a PDA, a significant part of the light in the spectral range of the PS absorption band can pass through the layer without participating in the PDA process.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a PS with 8 positive charges, octacationic phthalocyanine (ZnPcChol 8 ), and two bacteriochlorins with 4 and 8 positive charges, tetracationic ((3-PyBrE) 4 BCBr 4 ) and octacationic ((3-PyEPy) 4 BCBr 8 ), were all applied on P. aeruginosa in concentration of 250 µM, and tetracationic bacteriochlorin showed the strongest PDI effect (5-log CFU reduction on biofilm) with the smallest dose of light applied (20 J/cm 2 ) [139]. On the other hand, a complete eradication of the biofilms was achieved with phthalocyanine, although a high dose of light was required (100 J/cm 2 ), so the authors concluded that its high photostability contributed to the success of this PS, given that bacteriochlorins, in particular (3-PyBrE) 4 BCBr 4 , showed rapid and significant photodegradation with increased doses of light [139].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…They have a shortened length of alkylene chains (from 4 to 2 methylene links). These bacteriochlorins easily penetrate the cell wall, providing high photodynamic inactivation of Gram-positive and Gramnegative bacteria, including in the form of biofilms [4]. At the same time, they do not have a pronounced tendency to aggregate in a wide range of concentrations (up to 100 µM).…”
Section: Introductionmentioning
confidence: 99%